High Competence Faced by KFC Malaysia - Sin, Lim Kai; Kee, Daisy Mui Hung; Shin, Shirlin Teoh Keo; Qing, Low Tze; Ying, Ong Jia (AIBPM Publisher, 2019)
Fried chicken is one of the most favourite food in Malaysia while other types of fast food were also acquainted to attract consumers. The company’s lead in Malaysia’s fast food industry is KFC Holdings (M) Berhad, a subsidiary of QSR Brand (M) Holdings Berhad, attributed to its dominant presence specialises in fried chicken. The research question can be defined as following: How KFC compete and survive among all fast food restaurant in Malaysia? This research aims to understand the high competence issues faced by KFC Malaysia and recommend strategies to solve the problems. Using primary and secondary data, collect responds from Google Form and obtain data via Internet, this study analyses competitions and challenges confronted by KFC Malaysia. In this study, KFC Malaysia faces high competition in fast food industry, poor services from staff and lack of attractive promotion issues. Launch and promote new products based on consumers’ taste, ways to improve service quality of staff and promotional methods to increase sales were suggested to solve these problems. The main competitor of KFC Malaysia currently is McDonald’s. Keywords: KFC Malaysia, fast food industry, high competition, recommendations, improvements, promotions.